1998
DOI: 10.1073/pnas.95.11.6480
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain neurotransmitter receptors in transgenic mice expressing a portion of an abnormal human Huntington disease gene

Abstract: Loss of neurotransmitter receptors, especially glutamate and dopamine receptors, is one of the pathologic hallmarks of brains of patients with Huntington disease (HD). Transgenic mice that express exon 1 of an abnormal human HD gene (line R6͞2) develop neurologic symptoms at 9-11 weeks of age through an unknown mechanism. Analysis of glutamate receptors (GluRs) in symptomatic 12-week-old R6͞2 mice revealed decreases compared with age-matched littermate controls in the type 1 metabotropic GluR (mGluR1), mGluR2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
350
2
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 473 publications
(390 citation statements)
references
References 42 publications
32
350
2
4
Order By: Relevance
“…These mice, and in particular the R6/2 line, have an early onset of symptoms and a fast progression of the disease, showing a life expectancy of approximately 12 to 17 weeks, depending on the colony. The phenotype and neuropathology observed in these mice replicate several features observed in humans, including a progressive motor Luesse et al, 2001;Bolivar et al, 2003Bolivar et al, , 2004 and cognitive impairment Murphy et al, 2000), weight loss, decreased striatal and brain size (Mangiarini et al, 1996), ubiquitinated nuclear and cytoplasmic inclusions of the mutant protein (Davies et al, 1997;Li et al, 1999), altered levels of neurotransmitters (for review see Cha, 2000) and their receptors (Cha et al, 1998), altered gene expression (Luthi-Carter et al, 2000Zucker et al, 2005), diabetes (Hurlbert et al, 1999;Luesse et al, 2001;Andreassen et al, 2002;Björkqvist et al, 2005), which was previously reported in 10-25% of HD patients (Podolsky et al, 1972;Farrer, 1985), as well as several other neuroendocrine changes for review see Petersén and Björkqvist, 2006), and premature death (Mangiarini et al, 1996). Interestingly, both R6/2 (Gil et al, 2004 and R6/1 (Lazic et al, 2004(Lazic et al, , 2006 mice show a specific decrease in hippocampal cell proliferation and neurogenesis, which may account for some of their cognitive deficits (see below).…”
Section: Introduction -The R6 Micesupporting
confidence: 59%
“…These mice, and in particular the R6/2 line, have an early onset of symptoms and a fast progression of the disease, showing a life expectancy of approximately 12 to 17 weeks, depending on the colony. The phenotype and neuropathology observed in these mice replicate several features observed in humans, including a progressive motor Luesse et al, 2001;Bolivar et al, 2003Bolivar et al, , 2004 and cognitive impairment Murphy et al, 2000), weight loss, decreased striatal and brain size (Mangiarini et al, 1996), ubiquitinated nuclear and cytoplasmic inclusions of the mutant protein (Davies et al, 1997;Li et al, 1999), altered levels of neurotransmitters (for review see Cha, 2000) and their receptors (Cha et al, 1998), altered gene expression (Luthi-Carter et al, 2000Zucker et al, 2005), diabetes (Hurlbert et al, 1999;Luesse et al, 2001;Andreassen et al, 2002;Björkqvist et al, 2005), which was previously reported in 10-25% of HD patients (Podolsky et al, 1972;Farrer, 1985), as well as several other neuroendocrine changes for review see Petersén and Björkqvist, 2006), and premature death (Mangiarini et al, 1996). Interestingly, both R6/2 (Gil et al, 2004 and R6/1 (Lazic et al, 2004(Lazic et al, , 2006 mice show a specific decrease in hippocampal cell proliferation and neurogenesis, which may account for some of their cognitive deficits (see below).…”
Section: Introduction -The R6 Micesupporting
confidence: 59%
“…We have previously observed decreases in metabotropic glutamate receptor mRNA in four-week-old and eight-week-old R6/2 mice (Cha et al 1998). Thus, in eight-week-old animals, there are already major alterations in the glutamate, dopamine and adenosine neurotransmitter systems, which have major importance in striatal function.…”
Section: Resultsmentioning
confidence: 99%
“…Expression profiles of genes known to be dysregulated in HD mouse models, including Darpp32, Drd2, Cnr1, Pde10a in the striatum and Bdnf promoter transcripts in the cortex, can be run as molecular markers of disease. QPCR methods to assess expression have been well described for these and other genes known to be dysregulated in the HD mouse models (Benn et al, 2008;Cha et al, 1999;Cha et al, 1998). In addition, measuring Htt mRNA levels using qPCR or alternative methods, such as branched DNA assay platforms is recommended to evalulate therapeutic intervention on Htt transcription levels (Kordasiewicz et al, 2012).…”
Section: Iii10 Molecular and Histological Outcomesmentioning
confidence: 99%